Host Serum Proteins as Potential Biomarkers of Bovine Tuberculosis Resistance Phenotype - Mazorra-Carrillo, Jorge Luis; Alcaraz-López, Omar Antonio; López-Rincón, Gonzalo; Villarreal-Ramos, Bernardo; Gutiérrez-Pabello, José A.; Esquivel-Solís, Hugo (Frontiers in Veterinary Science, 2021)
Eradication of bovine tuberculosis (bTB) continues to be a worldwide challenge. The lack of reliable vaccines dampens the control and eradication programs of Mycobacterium bovis infection and spread. Selection and breeding of cattle resistant to M. bovis infection would greatly enhance the effectiveness of bTB eradication programs. Here, we have evaluated the potential of serum proteins as biomarkers of cattle resistance to bTB in Holstein-Friesian cows, 6-8-year-old, born and raised in similar conditions in herds with bTB prevalence >30%. Serum proteins obtained from uninfected cows (bTB-resistant; R) were compared to those from infected cows (bTB-susceptible; S), defined by a negative or positive bTB diagnosis, respectively. bTB diagnosis included: (i) single intradermal (caudal fold) tuberculin test, (ii) whole blood IFN-gamma test, (iii) gross visible lesions in lymph nodes and lungs by inspection at the abattoir, and (iv) a bacteriological culture for M. bovis. Using 2D-GE and LC-ESI-MS/MS, we found higher expression levels of primary amine oxidase (AO), complement component 5 (C5), and serotransferrin (TF) in R cattle than S cattle. In-house developed and standardized ELISAs for these novel biomarkers showed the best sensitivities of 72%, 77%, 77%, and specificities of 94%, 94%, 83%, for AO, C5, and TF, respectively. AUC-ROC (95% CI) values of 0.8935 (0.7906 to 0.9964), 0.9290 (0.8484 - 1.010), and 0.8580 (0.7291 - 0.9869) were obtained at cut-off points of 192.0 ng/mL, 176.5 ng/ml, and 2.1 mg/mL for AO, C5, and TF, respectively. These proteins are involved in inflammatory/immunomodulatory responses to infections and may provide a novel avenue of research to determine the mechanisms of protection against bTB. Overall, our results indicate that these proteins could be novel biomarkers to help identify cattle resistant to bTB, which in turn could be used to strengthen the effectiveness of existing eradication programs against bTB.